ANALISIS KRIMINOLOGI KORUPSI ANGGOTA DPRD SUMUT TERKAIT LAPORAN PERTANGGUNGJAWABAN PELAKSANAAN APBD (Studi Kasus Korupsi Anggota DPRD Sumut) - Santoso Santoso; Marzuki Marzuki; Nelvitia Purba (Jurnal Ilmiah METADATA, 2021)
The form of corruption committed by members of the North Sumatra DPRD related to the accountability report of the Provincial Government's APBD in the 2012-2014 Fiscal Year is bribery or gratuity, which is related to the implementation of its functions and duties in making legislation (legislation), approving the budget ( budgeting), and supervision (controling) of the implementation of local government policies. Bribery as a criminal offense for corruption in the PTPK Law is regulated in several articles, namely: Article 5 paragraph (1) letters a and b, Article 11, Article 12 B, Article 13 of the Corruption Eradication Law. Corruption committed by DPRD members from a criminological perspective is a crime. Interpretation of crimes against an act that is categorized as a criminal act of corruption, because the act is deemed to have caused unrest for the community. Efforts to prevent and eradicate corruption, which are ideal in a criminological perspective, can be carried out in two ways, namely penal and non-penal efforts.